A numerical analysis for predicting the thermal conductivity of carbon nanotube reinforced copper-matrix nanocomposites - Afrooza, I.E. (EDP Sciences, 2014)
Thermal conductivity of carbon nanotubes (CNTs) copper-matrix nanocomposites was predicted by using numerical approach. In the present study, twenty representative volume elements (RVEs) were modeled by assuming that the CNTs are distributed homogeneously in the copper (Cu) matrix. It is assumed that each RVE contains different pattern of CNTs distribution while the direction, diameter and length of CNTs are held constant. The effect of the CNTs-matrix interfacial resistance was also negligible. Therefore, it was observed that the predicted values of thermal conductivity would reach to the upper-bound rule of mixtures. Â© 2014 Owned by the authors, published by EDP Sciences.